Damage to the Cardiovascular System in Patients with SARS-CoV-2 Coronavirus Infection. Part 1: Predictors of the Development of an Unfavorable Prognosis - V. I. Podzolkov; A. I. Tarzimanova; A. E. Bragina; I. I. Shvedov; E. E. Bykova; A. A. Ivannikov; L. V. Vasilyeva (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the effect of sinus tachycardia and reduced left ventricular ejection fraction (LVEF) on the prognosis of patients with a verified diagnosis of a new coronavirus infection SARS-CoV-2.Material and methods. The study included 1,637 patients with a verified diagnosis of a new coronavirus infection SARS-CoV-2. The average age of the patients was 58.8±16.1 years. More than half of the patients admitted to the hospital had a history of cardiovascular diseases: hypertension was diagnosed in 915 (56%) patients, coronary artery disease – in 563 (34%), chronic heart failure – in 410 (25%). 294 (17.9%) patients suffered from diabetes mellitus. The unfavorable course of new coronavirus infection was assessed by the fact of being in the intensive care unit (ICU), the use of mechanical ventilation and death.Results. An unfavorable course of coronavirus infection was observed in 160 (9.8%) patients. Statistical analysis revealed that 341 (20.8%) patients with COVID-19 were diagnosed with sinus tachycardia, which required the appointment of pulse-reducing therapy. The occurrence of sinus tachycardia in patients with COVID-19 significantly increased the risk of death (odds ratio [OR] 1.248, confidence interval [CI] 1.038-1.499, p=0.018), increased the likelihood of mechanical ventilation use (OR 1.451, CI 1.168-1.803, p<0.001) and stay in the ICU (OR 1.440, CI 1.166-1.778, p<0.001).In 97 (5.9%) patients during hospital stay during echocardiography, a decrease in LVEF of less than 50% was diagnosed. A decrease in myocardial contractile function in patients with COVID-19 with high reliability increased the risk of death (OR 1.744, CI 1.348-2.256, p<0.001), increased the likelihood of using the mechanical ventilation (OR 1.372, CI 1.047-1.797, p=0.022) and stay in the ICU (OR 1.360, CI 1.077-1.716, p=0.010).Conclusion. The appearance of sinus tachycardia and reduced LVEF are in dependent predictors of the unfavorable course of COVID-19 in relation to factors such as death, the use of mechanical ventilation and the stay of patients in the ICU. Early pharmacological correction of cardiovascular lesions should be one of the goals of the management theese patients.